Development of a heat-shock inducible gene expression system in the red alga Cyanidioschyzon merolae. - Nobuko Sumiya (PLoS ONE, 2014)
The cell of the unicellular red alga Cyanidioschyzon merolae contains a single chloroplast and mitochondrion, the division of which is tightly synchronized by a light/dark cycle. The genome content is extremely simple, with a low level of genetic redundancy, in photosynthetic eukaryotes. In addition, transient transformation and stable transformation by homologous recombination have been reported. However, for molecular genetic analyses of phenomena that are essential for cellular growth and survival, inducible gene expression/suppression systems are needed. Here, we report the development of a heat-shock inducible gene expression system in C. merolae. CMJ101C, encoding a small heat shock protein, is transcribed only when cells are exposed to an elevated temperature. Using a superfolder GFP as a reporter protein, the 200-bp upstream region of CMJ101C orf was determined to be the optimal promoter for heat-shock induction. The optimal temperature to induce expression is 50°C, at which C. merolae cells are able to proliferate. At least a 30-min heat shock is required for the expression of a protein of interest and a 60-min heat shock yields the maximum level of protein expression. After the heat shock, the mRNA level decreases rapidly. As an example of the system, the expression of a dominant negative form of chloroplast division DRP5B protein, which has a mutation in the GTPase domain, was induced. Expression of the dominant negative DRP5B resulted in the appearance of aberrant-shaped cells in which two daughter chloroplasts and the cells are still connected by a small DRP5B positive tube-like structure. This result suggests that the dominant negative DRP5B inhibited the final scission of the chloroplast division site, but not the earlier stages of division site constriction. It is also suggested that cell cycle progression is not arrested by the impairment of chloroplast division at the final stage.